Periodizing the '80s: the 'differential of history' in Nicholson Baker's The Mezzanine - Thompson, Graham (Johns Hopkins University Press, 2011)
This essay examines how Nicholson Baker’s The Mezzanine shifts engagement with the details of the material world consistently onto the axis of temporality and how, in so doing, it fashions a theory of periodization in which historical and social trends and events are relegated in importance. Asking how the detail or moment might both alter an understanding of the general and spread time to infinite proportions, The Mezzanine casts doubt on the process of periodizing by way of metonymy and synecdoche and offers instead a contingent and improvised version of the 1980s.